Pengaruh Kepercayaan Terhadap Loyalitas Wakif Dalam Membayar Wakaf Tunai Pada Kementerian Agama Tanggamus - Sulaiman Sulaiman; Wulandari Wulandari (Dinar Islamic Review, 2020)
This study aims to determine the effect of trust on the loyalty of wakif paying cash waqf at the Ministry of Religion (Kemenag) Tanggamus (Case study at MAN 1 Kota Batu, Kota Agung-Tanggamus). The research method used is quantitative research. Data collection techniques using observation, documentation and questionnaires distributed to the public directly. A sample of 150 respondents was taken and then analyzed using multiple linear regression analysis using purposive sampling technique. The results of simple linear regression analysis concluded that there was a positive and significant effect of trust on the loyalty of waqf paying cash waqf at the Ministry of Religion of Tanggamus and the rest was influenced by other variables outside this model. The expected implication is that the government through the Ministry of Religion encourages socialization to increase the trust of Wakif throughout Indonesia.